Iceland : Staff Report for First Review under Stand-By Arrangement and Requests for Extension of the Arrangement, Waivers of Nonobservance of Performance Criteria, and Rephasing of Access. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the First Review Under the Stand-By Arrangement for Iceland. Post-crisis dynamics has followed the expected pattern: a sharp drop in GDP, rapid decline in inflation, shift of the current account to balance, and gradual stabilization of currency and financial markets. Several quantitative and structural program targets were missed. The authorities and IMF staff have agreed that a faster pace of fiscal adjustment and more gradual pace of capital account liberalization would be the key toward preserving stability and sustainability.